The wellbeing of adolescents and the role of greenness: A cross-sectional study among Italian students - Scaioli, Giacomo; Squillacioti, Giulia; Bersia, Michela; Bellisario, Valeria; Borraccino, Alberto; Bono, Roberto; Dalmasso, Paola; Lemma, Patrizia (Frontiers in Public Health, 2023)
Introduction Adolescence is a critical period of life, and the level of wellbeing acquired during this stage might have an influence on health status in adulthood. The wellbeing of adolescents is associated with both biological and environmental determinants. To date, few studies have evaluated the effect of exposure to urban green spaces (i.e., greenness) on adolescents' wellbeing. Therefore, the aim of this study is to assess the association between exposure to greenness and the wellbeing of adolescents, accounting for the level of urbanization surrounding schools. Methods In the frame of the 2018 Italian Health Behaviour in School-aged Children (HBSC), we analyzed cross-sectional data from the Piedmont Region. Exposure to greenness was quantified by the Normalized Difference Vegetation Index (NDVI). Schools were geocoded, and a fixed buffer (radius 1,500 m) centered on each school was then built to enable average NDVI calculations. Adolescents' wellbeing was assessed by self-reported psychological, somatic, and psychosomatic health complaints as follows. Respondents were asked how often, in the last 6 months, they had experienced: (a) headache, (b) stomachache, (c) backache, (d) dizziness, (e) feeling low, (f) irritability or bad temper, (g) feeling nervous, and (h) difficulties getting to sleep using the HBSC Symptom Checklist (HBSC-SCL), an eight-item tool. Multivariable, multilevel logistic regression models tested the association between exposure to NDVI and psychosomatic, somatic, and psychological health complaints, one at a time, using schools as a random intercept. Results In total, 2065 subjects (47.6% girls) aged 11 (48.4%) and 13 (51.6%) years were involved. Greenness was found to be inversely associated with reported psychosomatic (OR 0.72, 95% CI: 0.53–0.98) and psychological health complaints (OR 0.67, 95% CI: 0.49–0.92) in boys only, adjusting for age, urbanization level, and socioeconomic status, and stratifying by gender. Discussion Our results support the implementation of future policies for urban environmental design supporting the increase of green spaces, as suggested by the United Nations Sustainable Development Goals. Further studies are needed to confirm our findings.